Dielectric Function of Matrix Disperse Systems with Metallic Inclusions. Account of Multipole Interaction between Inclusions - Grechko, L. G.; Blank, A. Ya.; Motrich, V. V.; Pinchuk, A. A.; Garanina, L. V. (Видавничий дім «Академперіодика», 2012)
Dielectric Function of Matrix Disperse Systems with Metallic Inclusions. Account of Multipole Interaction between Inclusions